Estimating tree density in oak savanna-like lsquo;dehesa’ of southern Spain from SPOT data - JOFFRE, R.; LACAZE, B. (International Journal of Remote Sensing, 1993)
Abstract The main objective of this study was to establish a method of estimating tree density in savanna-like vegetation systems using the highest spatial resolution available from satellite data (SPOT-1 panchromatic = 10 m resolution) based on the assumption that for sparse trees on a contrasting herbaceous background, spatial filters may provide a direct mapping of tree cover. The study was performed in the ?dehesas? oak-woodland of southern Spain. This particular landscape is characterized by the presence of scattered evergreen oak trees (Quercus ilex and Q. suber) whose density ranges from 0 to 80 even-aged mature trees per hectare which gives the appearance of a savanna-like vegetation. Tree density can be accurately estimated by SPOT-1 panchromatic data after numerical filtering. This method allows the mapping of tree density of the dehesas, a key parameter reflecting the functional vegetation-soil-climate equilibrium which exists for both woody and herbaceous strata.
doi: 10.1080/01431169308904368doi: 10.1080/01431169308904368The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Dehesa; oak; savanna-like; SOPT data; southern Spain; tree density